2015
DOI: 10.1097/pcc.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Pediatric Resuscitation Performance After a Simulation-Based Mastery Learning Session

Abstract: Residents displayed significant improvements in resuscitation performance after a single simulation-based mastery learning session, but performance declined over time, with less than 60% retaining mastery-level performance at 6 months. Our results suggest that relatively frequent refresher training is needed after a single simulation-based mastery learning session. Additional research is needed to determine the duration of performance retention following any specific simulation-based mastery learning intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…Randomised controlled trials of newborn resuscitation training infrequently report clinical outcomes and a cluster randomised approach may be a more suitable trial design to assess these outcomes 1. It has been established that newborn resuscitation skills can deteriorate over time, therefore we cannot conclude that the improvement shown in this trial will be retained on a long-term basis 23 24. However, Schilleman et al demonstrated that a reduction in newborn mask leak immediately after training was maintained 3 weeks later 25.…”
Section: Discussionmentioning
confidence: 94%
“…Randomised controlled trials of newborn resuscitation training infrequently report clinical outcomes and a cluster randomised approach may be a more suitable trial design to assess these outcomes 1. It has been established that newborn resuscitation skills can deteriorate over time, therefore we cannot conclude that the improvement shown in this trial will be retained on a long-term basis 23 24. However, Schilleman et al demonstrated that a reduction in newborn mask leak immediately after training was maintained 3 weeks later 25.…”
Section: Discussionmentioning
confidence: 94%
“…Similar studies of intensive simulation-based mastery learning have demonstrated skills retention up to 12–14 months among Internal Medicine residents,15 16 whereas shorter (1–2 hours) sessions among paediatric residents resulted in linear decline of performance, with 92% retention at 2 months and 56% at 6 months 17. While this curriculum was not designed as mastery training, we noted overall retention of improvements through the 4–6 month follow-up assessment, suggesting that shorter sessions among paediatric residents may retain greater efficacy than previously suggested.…”
Section: Discussionmentioning
confidence: 72%
“…When evaluating the success of an educational intervention, the recognized confounder of skill decay must be considered. Skill and knowledge can quickly decay after simulation‐based education, with one study reporting decay as early as 2 weeks . Educational theory suggests the benefit of simulation stems from repetitive practice .…”
Section: Discussionmentioning
confidence: 99%
“…Educational theory suggests the benefit of simulation stems from repetitive practice . Yet even with repetition, skills and knowledge decay, Braun et al . demonstrated that learner performance declined at 2 months even with repetitive practice until “mastery‐level performance” was met.…”
Section: Discussionmentioning
confidence: 99%